Validation of an assessment and monitoring instrument for the care of patients in imminent death situation admitted in internal medicine wards - Carneiro, Rui (2022)
Background: In Portugal, two thirds of deaths occur in the hospital and it is estimated that these numbers will increase considerably in the coming decades. The proper organization of care at this stage promotes peaceful deaths and catalyzes healthy bereavements. There is no validated instrument that supports health teams in the organization of care in the situation of imminent death syndrome. Aim(s): We propose the validation of an instrument for organizing care for patients in the last hours or days of life in Internal Medicine wards. Methods: We recruited an incidental sample of Internal Medicine doctors with Competence in Palliative Medicine. We will evaluate the response to a semi-structured questionnaire of the Delphi rounds type, evaluating the degree of agreement with the principles proposed by the instrument, which was already validated in accordance with the best international practices and derived from the best scientific evidence by the International Collaborative for the Best for the Dying Person Results: The Delphi rounds are underway Conclusions: The validation of this instrument will be the basis for the subsequent development of a national audit on the subject and the mainstay for the construction of a training model for national Internal Medicine based on the proposed principles of action, that constitutes the main goals of the MiMI Project (Morte iminente em Medicina Interna) of the Portuguese Society of Internal Medicine.